Looking closely across the desert - Serafini, Frank (Tonawanda, NY : Kids Can Press, 2008)
Extreme close-up photographs challenge readers to guess the identity of the desert plant, animal, or landscape feature it depicts, each followed by a description.
5.0
K-3
Keywords: Desert animals -- Juvenile literature; Desert plants -- Juvenile literature; Photography, Close-up -- Juvenile literature; Desert animals; Desert plants; Photography, Close-up.; Close-up photography; Desert animals; Desert plants